Modernization as ideology : American social science and "nation building" in the Kennedy era - Latham, Michael E. (New Cold War history., 2000)
A discussion of the intellectual and cultural dimensions of the Cold War, revealing how social science theory helped shape American foreign policy during the Kennedy administration. It demonstrates how the concept of global modernization became a motivating ideology behind policy decisions.